Can innovative digital collaborations help overcome barriers to intersectoral collaboration?. (30th September 2020) - Nordström, C; Kumar, B
Abstract: Issue: Health in all policies is desirable, but moving from the silos approach is a challenge for health care systems. New health policies require more cooperation and broader collaboration between governmental, private and volunteer sector, as well as across professions. Though it is key to implementation of national policies and long-term public health work at the local level, intersectoral collaboration remains elusive. Professionals working with public health and migrant health across Norway often work independently of each other and other sectors. Description of the Problem: Evaluation of the Norwegian network for migrant friendly hospitals showed that with the opportunity to meet and share experiences, participants used the new knowledge and network in developing their practice and organisation of services. They experienced greater support to challenge status quo in their institutions. However, fear of making the network "too big to handle" is a barrier to creating intersectoral network. In a recent survey (2017), health personnel ask for digital solutions for finding resources and support in their practice to give better health care to immigrant patients. Results: The newly (2020) knowledge HUB part of JAHEE actions brings stakeholders together at the local, regional and national level, ensuring access to the same knowledge, increase evidence based decisions among stakeholders when choosing interventions on the local, regional and national level, including sharing of good practices and promising initiatives at a national level so that they can be replicated. Lessons: Professional networks that are coordinated and collaborative are important for development of services and implementation of measures for migrant health. However, expanding them across sectors and fields may create challenges. Combining sectoral networks with a common digital platform may overcome some of these challenges. Key messages: Exploiting the potential of collaborative digital solutions may help overcome some barriers to intersectoral approach to migrant health. Coordinated collaborative professional networks can support the participants in developing their practice and organisation of services for migrants.